Ocular higher-order aberrations and mesopic pupil size in individuals screened for refractive surgery - Hashemian, Seyed Javad (International Journal of Ophthalmology Press, 2012)
AIM: To study the distribution of ocular higher-order aberrations(HOAs) and mesopic pupil size in individuals screened for refractive surgery. METHODS: Ocular HOAs and mesopic pupil size were studied in 2 458 eyes of 1 240 patients with myopia, myopic astigmatism and compound myopic astigmatism and 215 eyes of 110 patients with hyperopia, hyperopic astigmatism and compound hyperopic astigmatism using the Zywave aberrometer (Busch& Lomb). All patients had correctable refractive errors without a history of refractive surgery or underlying diseases. Root-mean-square values of HOAs, total spherical aberration, total coma and mesopic pupil size were analyzed. Ocular HOAs were measured across a ≥ 6.0 mm pupil, and pupil size measurements were performed under the mesopic condition. RESULTS: The mean values of HOAs, total spherical aberration and total coma in the myopic group were 0.369µm, ±0.233, 0.133± 0.112µm and 0.330±0.188µm, respectively. In the hyperopic group the mean values of HOAs, total spherical aberration and total coma were 0.418µm ±0.214, 0.202±0.209µm and 0.343±0.201µm, respectively. Hyperopes showed greater total HOAs (P<0.01) and total spherical aberration (P<0.01) compared to myopes. In age-matched analysis, only the amount of total spherical aberration was higher in the hyperopic group (P=0.05). Mesopic pupil size in the myopic group was larger (P≤0.05). CONCLUSION: The results suggested that significant levels of HOAs were found in both groups which are important for planning refractive surgeries on Iranians. There were significantly higher levels of total spherical aberration in hyperopes compared to myopes. Mesopic pupil size was larger in myopic group.